An Experience with Software Engineering Education Using a Software Process Improvement Game - Peixoto, Daniela C. C.; Resende, Rodolfo F.; Pádua, Clarindo Isaías P. S. (Higher Education for All. From Challenges to Novel Technology-Enhanced Solutions, 2018)
Educational games offer different ways for representing complex themes. However, creating a game that precisely addresses the subject being taught and effectively provides students’ learning and engagement is a complicated task. With this in mind, we researched and created an educational game for improving students’ Software Process Improvement (SPI) knowledge. The aim of this game is to bring practices from the software development industry to the students. In an attempt to provide a better guidance, this work describes the issues and challenges associated with the creation and validation process of a Software Engineering educational game. We adopted an incremental and iterative approach, where each step involves different knowledge, allowing us to point out a set of important aspects that should be taken into account during the development. These aspects can guide new developers and instructors in the design and selection of educational games.